A plant‐unique ESCRT component, FYVE4, regulates multivesicular endosome biogenesis and plant growth. Issue 1 (22nd April 2021) - Liu, Chuanliang; Zeng, Yonglun; Li, Hongbo; Yang, Chao; Shen, Wenjin; Xu, Min; Xiao, Zhidan; Chen, Tongsheng; Li, Baiying; Cao, Wenhan; Jiang, Liwen; Otegui, Marisa S.; et al.
Summary: During evolution, land plants generated unique proteins that participate in endosomal sorting and multivesicular endosome (MVE) biogenesis, many of them with specific phosphoinositide‐binding capabilities. Nonetheless, the function of most plant phosphoinositide‐binding proteins in endosomal trafficking remains elusive. Here, we analysed several Arabidopsis mutants lacking predicted phosphoinositide‐binding proteins and first identified fyve4‐1 as a mutant with a hypersensitive response to high‐boron conditions and defects in degradative vacuolar sorting of membrane proteins such as the borate exporter BOR1‐GFP. FYVE4 encodes a plant‐unique, FYVE domain‐containing protein that interacts with SNF7, a core component of ESCRT‐III (Endosomal Sorting Complex Required for Transport III). FYVE4 affects the membrane association of the late‐acting ESCRT components SNF7 and VPS4, and modulates the formation of intraluminal vesicles (ILVs) inside MVEs. The critical function of FYVE4 in the ESCRT pathway was further demonstrated by the strong genetic interactions with SNF7B and LIP5 . Although the fyve4‐1, snf7b and lip5 single mutants were viable, the fyve4‐1 snf7b and fyve4‐1 lip5 double mutants were seedling lethal, with strong defects in MVE biogenesis and vacuolar sorting of ubiquitinated membrane proteins. Taken together, we identified FYVE4 as a novel plant endosomal regulator, which functions in ESCRTing pathway to regulate MVE biogenesis.